A Boyhood Dream Realized : Half a Century of Texas Culture, One Newspaper Column at a Time - Pettit, Burle, 1934- (Book collections on Project MUSE., 2019)
This collection of columns from the Lubbock Avalanche-Journal is Texas Folklore Society Extra Book #27. The editorial columns included herein tell stories, and tell about telling stories. They also reflect boyhood dreams ... and foolishness, fears, beliefs, customs, traditions, and sometimes things that are no longer part of our culture but we wish were. All reflect what was--and for many, still is--important. If ""the traditional knowledge of a culture"" is how we define what folklore is, this volume provides an intimate look at the folklore of Lubbock, Texas, and the greater area of the So